Early optimized pharmacological treatment in patients with depression and chronic pain. (23rd April 2023) - Oluboka, Oloruntoba J.; Katzman, Martin A.; Habert, Jeffrey; Khullar, Atul; Oakander, Margaret A.; McIntosh, Diane; McIntyre, Roger S.; Soares, Claudio N.; Lam, Raymond W.; Klassen, Larry J.; Tanguay, Robert
Abstract: Major depressive disorder (MDD) is the leading cause of disability worldwide. Patients with MDD have high rates of comorbidity with mental and physical conditions, one of which is chronic pain. Chronic pain conditions themselves are also associated with significant disability, and the large number of patients with MDD who have chronic pain drives high levels of disability and compounds healthcare burden. The management of depression in patients who also have chronic pain can be particularly challenging due to underlying mechanisms that are common to both conditions, and because many patients with these conditions are already taking multiple medications. For these reasons, healthcare providers may be reluctant to treat such patients. The Canadian Network for Mood and Anxiety Treatments (CANMAT) guidelines provide evidence-based recommendations for the management of MDD and comorbid psychiatric and medical conditions such as anxiety, substance use disorder, and cardiovascular disease; however, comorbid chronic pain is not addressed. In this article, we provide an overview of the pathophysiological and clinical overlap between depression and chronic pain and review evidence-based pharmacological recommendations in current treatment guidelines for MDD and for chronic pain. Based on clinical experience with MDD patients with comorbid pain, we recommend rapidly and aggressively treating depression according to CANMAT treatment guidelines, using antidepressant medications with analgesic properties, while addressing pain with first-line pharmacotherapy as treatment for depression is optimized. We review options for treating pain symptoms that remain after response to antidepressant treatment is achieved.